2021
DOI: 10.1093/brain/awab191
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal changes in dopamine, neuromelanin and iron characterizing Parkinson’s disease

Abstract: In Parkinson’s disease, there is a progressive reduction in striatal dopaminergic function, and loss of neuromelanin-containing dopaminergic neurons and increased iron deposition in the substantia nigra. We tested the hypothesis of a relationship between impairment of the dopaminergic system and changes in the iron metabolism. Based on imaging data of patients with prodromal and early clinical Parkinson’s disease, we assessed the spatiotemporal ordering of such changes and relationships in the sensorimotor, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 76 publications
2
79
0
Order By: Relevance
“…Several mutations in ferroptosis genes have been linked to PD (Table 1), including DJ-1, autosomal recessive PD gene, that encodes a negative modulator of ferroptosis [16]. Moreover, the characteristics of ferroptosis induction are highly consistent with the pathological changes observed in PD patients, including increased iron content [4,5], lipid peroxidation [17][18][19], and defects in the antioxidant system such as decreased levels of cystine/ glutamate antiporter (xCT) [20], glutathione (GSH) [21], DJ-1 (that maintains cysteine and GSH biosynthesis) [16], and CoQ10 [22]. Furthermore, ferroptosis was observed in different PD cellular and animal models such as SH-SY5Y cells treated with MPP + and 6-OHDA, and MPTP-lesioned mice [8][9][10].…”
Section: Evidence Of Ferroptosis In Pd Pathologymentioning
confidence: 89%
See 1 more Smart Citation
“…Several mutations in ferroptosis genes have been linked to PD (Table 1), including DJ-1, autosomal recessive PD gene, that encodes a negative modulator of ferroptosis [16]. Moreover, the characteristics of ferroptosis induction are highly consistent with the pathological changes observed in PD patients, including increased iron content [4,5], lipid peroxidation [17][18][19], and defects in the antioxidant system such as decreased levels of cystine/ glutamate antiporter (xCT) [20], glutathione (GSH) [21], DJ-1 (that maintains cysteine and GSH biosynthesis) [16], and CoQ10 [22]. Furthermore, ferroptosis was observed in different PD cellular and animal models such as SH-SY5Y cells treated with MPP + and 6-OHDA, and MPTP-lesioned mice [8][9][10].…”
Section: Evidence Of Ferroptosis In Pd Pathologymentioning
confidence: 89%
“…Activated glia may act as 'double-edged swords' because they can exert neuroprotective effects by releasing neurotrophic factors and phagocytosis, while mediating neuronal damage by releasing proinflammatory cytokines [3]. Brain imaging and pathological studies have shown correlations between iron deposition in the SNpc of PD patient brains and DA neuronal loss [4,5], indicating that imbalance of iron homeostasis may be a factor closely associated with neuronal death in PD. This type of iron-dependent cell death is termed ferroptosis [6].…”
Section: Glia Activation and Iron Accumulation In The Pathogenesis Of Pdmentioning
confidence: 99%
“…Parkinson Disease ↓ Fe in serum/plasma [107] ↑ Fe in substantia nigra [108,109] ↑ Fe in neurons and adjacent neuropil, microglia, perivascularly in extracellular deposits [110][111][112] Fe bound to neuromelanin in dopaminergic neurons [112,113] Alzheimer Disease ↓ Fe in serum/plasma [114][115][116] ↑ Fe in (mostly temporal) cortex, globus pallidus, caudate, putamen [117][118][119][120][121][122] ↑ Fe in amyloid plaques, microglia, along myelinated fibers [117,[123][124][125] Fe bound to amyloid partially composed of magnetite nanoparticles [126,127] Amyotrophic Lateral Sclerosis ↑ ferritin, ↓ transferrin in serum [128] ↑ Fe in liver, kidneys [129] ↑ Fe in spinal cord [130,131] ↑ Fe in motor cortex, caudate, subthalamic nucleus, globus pallidus, substantia nigra, red nucleus [132][133][134] ↑ Fe in spinal cord neuron nuclei [135] ↑ Fe in microglia in motor cortex [136] n.a.…”
Section: Macroscopic Cellular Subcellularmentioning
confidence: 99%
“…Apart from pathological protein inclusions, the brain is affected by a progressive alteration of its neurochemistry as well as an imbalance of numerous neurotransmitters that disturb the activity of neurons and glial cells. The progressive depletion of NA and dopamine (DA) is associated with ageing ( Manaye et al, 1995 ; Volkow et al, 1998 ; Beardmore et al, 2021 ) and the onset of NDDs such as AD and PD ( Weinshenker, 2018 ; Biondetti et al, 2021 ). A local change of availability of NA or DA could strongly alter the responses of astrocytes in NDDs and favor their neurotoxicity.…”
Section: Breaking Bad: When Do Astrocytes Become Toxic To Surrounding...mentioning
confidence: 99%